A green dragon skin-attapulgite composite material, a preparation method and application thereof

CN118594475BActive Publication Date: 2026-10-30LANZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410870671.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-01
Publication Date
2026-10-30
Estimated Expiration
2044-07-01

AI Technical Summary

Technical Problem

[0009]基于此,针对现有技术中材料对四环素类抗生素吸附效率低的问题,本发明提供一种青龙衣-凹凸棒复合材料,进一步提供其制备方法,以及其在四环素类抗生素中的应用,该青龙衣-凹凸棒复合材料相比于单独的青龙衣生物炭材料、单独的凹凸棒材料,以及相比于未经活化的复合材料,在废水特别是水产畜禽养殖废水中具有显著提高的四环素类抗生素的吸附能力,且实现水产畜禽废水中抗生素的低成本、高效率吸附

Benefits of technology

[0040](1)本发明提供一种新的复合材料,即包含特定含量的来自青龙衣的生物炭、凹凸棒以及锌离子的青龙衣-凹凸棒复合材料,该复合材料相对于不包含锌离子而仅包含青龙衣的生物炭和凹凸棒的材料,针对四环素类抗生素具有显著提升的吸附性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118594475B_ABST
    Figure CN118594475B_ABST
Patent Text Reader

Abstract

The application discloses a Qinglongyi-attapulgite composite material, wherein the Qinglongyi-attapulgite composite material comprises biochar from Qinglongyi, attapulgite, the mass percentage of the attapulgite accounts for 30-60% of the Qinglongyi-attapulgite composite material, and zinc ions, the mass percentage of the zinc ions accounts for 0.01-0.05% of the Qinglongyi-attapulgite composite material. The composite material has significantly improved adsorption performance for tetracycline antibiotics compared with a material containing only biochar and attapulgite of Qinglongyi without containing zinc ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of antibiotic adsorption technology, and more specifically, relates to a dinoflagellate-attapulgite composite material as an antibiotic adsorbent, its preparation method and application. Background Technology

[0002] Wastewater generated from daily human activities, livestock and aquaculture, pharmaceutical production, and hospitals, if not effectively treated, can leave residual antibiotics that flow into rivers, soil, and other environmental media, entering the ecosystem and causing harm to both humans and nature. Antibiotics have become a boon for improving human and animal health, used to treat diseases, act as growth promoters, and improve feed efficiency. Tetracycline antibiotics are fast-acting bacteriostatic agents, possessing bactericidal effects at high concentrations. They have a broad antibacterial spectrum and are inexpensive. In aquaculture, they are typically administered orally through feed or by soaking in the feed. This widespread use of tetracycline antibiotics in livestock and aquaculture often results in them being unable to be absorbed by organisms and directly entering the aquatic environment, polluting water bodies.

[0003] Currently, the main technologies used to address tetracycline antibiotic pollution in livestock and aquaculture wastewater include ultraviolet photocatalysis, biochar, and pharmaceutical sludge control. However, the high cost of these technologies means that some are only used in simple laboratory settings and are rarely applied in complex real-world livestock and aquaculture environments.

[0004] In recent years, the main methods for treating tetracycline antibiotics have been photocatalysis, adsorption, and microbial degradation. Among these, photocatalysis has been applied in the construction of two-dimensional / one-dimensional ZnIn2S4 / attapulgite structures by anchoring ZnIn2S4 nanosheets on the surface of attapulgite. These structures were used for the catalytic removal of tetracycline hydrochloride (TC) under visible light irradiation, achieving a removal rate of 82.1% (Zhang, G., Li, S., Li, Y., & Dong, X. (2023). 2D / 1D ZnIn2S4 / attapulgite hybrid materials for enhanced photocatalytic performance under visible light. Applied Clay Science, 246. doi:10.1016 / j.clay.2023.107162). Microbial degradation methods include: *Arthrobacter nicotianae*, a tetracycline-degrading bacterium, can reduce the concentrations of OTC and TET in pig and chicken manure, with a maximum reduction rate of 91.54% (Shi, Y., Lin, H., Ma, J., Zhu, R., Sun, W., Lin, X., Zhang, X. (2021). Degradation of tetracycline antibiotics by *Arthrobacter nicotianae* OTC-16. *Journal of Hazardous Materials*, 403.). Adsorption is an effective method for removing antibiotics from water, offering advantages such as ease of operation, low cost, and no secondary pollution. For example, CN115920842 A discloses the application of KMnO4 modified biochar (MBC) in tetracycline adsorption removal. Photocatalysis and microbial degradation methods require higher input costs and have more complex removal mechanisms; in contrast, adsorption is a simple and effective method for removing antibiotics from water.

[0005] Biochar is a widely derived material from agricultural waste, municipal solid waste, industrial organic waste, aquatic plants, and algae. It is an excellent biomass-derived adsorbent, and due to its surface aroma and functionality, it can be used to remove organic pollutants and antibiotics from livestock and aquaculture. Walnut husks, also known as "green dragon skin," are agricultural waste that floods the market every October. Due to improper utilization, they accumulate in large quantities in open areas, polluting soil and water bodies and impacting human health. However, as biochar, it can treat wastewater. For example, CN111821949A describes the preparation of nitrogen-phosphorus co-doped peanut shell biochar for antibiotic removal from wastewater, and CN115055159A describes the application of calcium-modified straw biochar for the simultaneous adsorption of phosphates and tetracyclines. While walnut husks are a type of high-quality biochar, their application in the adsorption and treatment of antibiotics in livestock and poultry wastewater is rarely seen.

[0006] Currently, China ranks among the world's leading countries in the distribution and abundance of attapulgite, with large quantities found in Gansu, Jiangsu, and Anhui provinces. It is a natural clay mineral, known for its low price, stable properties, low cost, and excellent physicochemical properties. Attapulgite is a hydrous magnesium-aluminate silicate clay mineral with a layered chain structure, possessing a large specific surface area and a wide pore size distribution. The preparation of adsorbent materials using a composite of attapulgite and biochar holds immense potential for the adsorption and removal of tetracycline antibiotics from wastewater, particularly from aquaculture and livestock farming wastewater.

[0007] However, the adsorption efficiency of biochar, attapulgite, or a combination of biochar and attapulgite as adsorbents still needs to be improved. Summary of the Invention

[0008] 1. The problem to be solved

[0009] Based on this, and addressing the problem of low adsorption efficiency of tetracycline antibiotics in existing materials, this invention provides a *Cyclocarya paliurus*-attapulgite composite material, further providing its preparation method and its application in tetracycline antibiotics. Compared with *Cyclocarya paliurus* biochar alone, attapulgite alone, and unactivated composite materials, this *Cyclocarya paliurus*-attapulgite composite material has a significantly improved adsorption capacity for tetracycline antibiotics in wastewater, especially aquaculture and livestock wastewater, and achieves low-cost, high-efficiency adsorption of antibiotics in aquaculture and livestock wastewater.

[0010] 2. Technical Solution

[0011] To solve the above problems, the technical solution adopted by the present invention is as follows:

[0012] The first aspect of this invention provides a *Gynostemma pentaphyllum*-attapulgite composite material, wherein, based on the weight of the *Gynostemma pentaphyllum*-attapulgite composite material, the *Gynostemma pentaphyllum*-attapulgite composite material comprises:

[0013] Biochar derived from the Azure Dragon Robe;

[0014] Attapulgite; the mass percentage of the attapulgite accounts for 30-60% of the patina-attapulgite composite material;

[0015] And zinc ions; the zinc ions account for 0.01 to 0.05% of the mass percentage of the diatomaceous earth-attapulgite composite material.

[0016] The zinc ion content range in the composite material of the present invention can ensure the efficient adsorption of antibiotics by the *Coprinus erinaceus*-attapulgite composite material. When the composite material contains no zinc ions or the zinc ion content is too high, the adsorption efficiency for antibiotics will decrease. Therefore, the present invention provides a *Coprinus erinaceus*-attapulgite composite material with a suitable range of zinc ion content for antibiotic adsorption.

[0017] As a preferred embodiment of any of the first aspects of the present invention, the zinc ions are derived from one or more of zinc nitrate, zinc chloride, zinc sulfate, and zinc perchlorate.

[0018] As a preferred embodiment of any aspect of the present invention, the mass ratio of biochar to attapulgite is 0.5 to 2:1. More preferably, it is 0.8 to 1.2:1, and most preferably, it is 1:1.

[0019] As a preferred embodiment of any of the first aspects of the present invention, the attapulgite accounts for 40 to 60% of the mass percentage of the tarpaulin-attapulgite composite material.

[0020] As a preferred embodiment of any of the first aspects of the present invention, the specific surface area of ​​the Qinglongyi-attapulgite composite material is not less than 60 cm². 2 / g, and further not less than 80cm 2 / g.

[0021] A second aspect of this invention provides a method for preparing a zigzag-attapulgite composite material, comprising the following steps:

[0022] The activation step involves activating attapulgite and scleroderma with zinc ions under hydrothermal conditions; wherein, hydrothermal refers to a chemical reaction carried out in a sealed pressure vessel, such as a reactor, using water as a solvent, under high temperature and high pressure conditions; and scleroderma refers to the powdered dried scleroderma.

[0023] The precursor preparation steps involve preparing a *Symplocos lucida*-attapulgite precursor using zinc ion-activated attapulgite and *Symplocos lucida*; and...

[0024] The calcination and carbonization step involves calcining and carbonizing the *Cynanchum paniculatum*-attapulgite precursor to obtain the *Cynanchum paniculatum*-attapulgite composite material.

[0025] As a preferred embodiment of any of the second aspects of the present invention, in the activation step, the mass ratio of attapulgite to cotoneaster is 0.5–2:1; and the mass ratio of zinc ions to attapulgite is 0.02–0.1:100. It should be noted that the proportion of zinc ions in the activation step has a significant impact on the adsorption performance of the cotoneaster-attapulgite composite material. When the proportion of zinc ions in the activation step is within the above range, the cotoneaster-attapulgite composite material is successfully synthesized and practically applied to the efficient adsorption and removal of tetracycline antibiotics. When the proportion of zinc ions in the activation step is high, for example, when the mass ratio of zinc ions to attapulgite is approximately 0.5:100, the adsorption performance of the obtained cotoneaster-attapulgite composite material decreases.

[0026] As a preferred embodiment of any of the second aspects of the present invention, in the activation step, the concentration of zinc ions is 0.05 to 0.2 mg / mL.

[0027] As a preferred embodiment of any of the second aspects of the present invention, in the activation step, the activation temperature is 100–150°C, and the activation time is 18–36 h. It should be noted that the activation temperature range has a significant impact on the adsorption performance of the *Gynostemma pentaphyllum*-attapulgite composite material. When the activation temperature is low, the adsorption effect of the prepared composite material is poor; when the activation temperature is high, for example above 550°C, the rod-like structure of the attapulgite collapses, leading to a sharp decrease in specific surface area and porosity, thereby affecting the adsorption performance and causing a decline in the adsorption performance of the obtained *Gynostemma pentaphyllum*-attapulgite composite material.

[0028] As a preferred embodiment of any of the second aspects of the present invention, in the activation step, the attapulgite is obtained by hydrothermal purification of attapulgite ore with sodium hexametaphosphate.

[0029] As a preferred embodiment of any of the second aspects of the present invention, in the activation step, the green walnut skin is obtained by freeze-drying the green walnut skin.

[0030] As a preferred embodiment of any of the second aspects of the present invention, in the calcination and carbonization step, the calcination and carbonization temperature is 450-500℃, and the calcination and carbonization time is 3-5 hours. It should be noted that the calcination temperature range has a significant impact on the adsorption performance of the *Cotinus coggygria*-attapulgite composite material. When the calcination and carbonization temperature is low, the specific surface area and pore size of the *Cotinus coggygria* are small, and the interstitial water in the attapulgite cannot be removed, thus affecting the adsorption performance. When the calcination and carbonization temperature is high, for example, above 550℃, the rod-like structure of the attapulgite collapses, resulting in a drastic reduction in the specific surface area and pore size, leading to a rapid decrease in adsorption performance and consequently a decrease in the adsorption performance of the obtained *Cotinus coggygria*-attapulgite composite material.

[0031] As a preferred embodiment of any of the second aspects of the present invention, in the calcination and carbonization step, an inert gas, particularly an N2 atmosphere, is used, and the heating rate is 5-10°C / min.

[0032] The third aspect of the present invention provides the application of the *Cotyledon tomentosa*-attapulgite composite material according to any embodiment of the first aspect of the present invention, or the *Cotyledon tomentosa*-attapulgite composite material prepared by any preparation method according to any one of the second aspects of the present invention, in the adsorption of antibiotics in wastewater.

[0033] As a preferred embodiment of any of the third aspects of the present invention, the wastewater is livestock and poultry aquaculture wastewater; the antibiotic is a tetracycline antibiotic.

[0034] As a preferred embodiment of any third aspect of the present invention, the tetracycline antibiotic is selected from one or two of tetracycline (TC) and oxytetracycline hydrochloride (OTC).

[0035] As a preferred embodiment of any of the third aspects of the present invention, the tetracycline antibiotic is selected from tetracycline and / or oxytetracycline hydrochloride.

[0036] As a preferred embodiment of any of the third aspects of the present invention, the dinoflagellate-attapulgite composite material can be recycled more than once, preferably more than five times. Even after being recycled more than five times, it still provides a high adsorption efficiency for tetracycline antibiotics.

[0037] As a preferred embodiment of any of the third aspects of the present invention, the dinosaur-attapulgite composite material is regenerated by calcination at 400-420°C under an inert gas atmosphere, particularly N2 atmosphere.

[0038] 3. Beneficial effects

[0039] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0040] (1) The present invention provides a new composite material, namely, a tantalizing-attapulgite composite material containing a specific amount of biochar from tantalizing leaves, attapulgite and zinc ions. Compared with materials that do not contain zinc ions but only contain tantalizing leaves biochar and attapulgite, the composite material has significantly improved adsorption performance for tetracycline antibiotics.

[0041] (2) The present invention provides a method for preparing a scabra-attapulgite composite material. First, zinc ions are used to activate scabra and attapulgite at a specific temperature to prepare an activated precursor. Then, the precursor is calcined and carbonized to obtain the scabra-attapulgite composite material. The composite material prepared by this pre-activation method has significantly improved adsorption performance for tetracycline antibiotics compared with the material that has not been activated by zinc ions.

[0042] (3) In the activation step of the preparation method of the Qinglongyi-attapulgite composite material of the present invention, the ratio of zinc ions to Qinglongyi and attapulgite, as well as the setting of the activation temperature, have an important influence on the adsorption performance of the composite material. When the proportion of zinc ions in the composite material is too high, for example, when the mass ratio of zinc ions to attapulgite is higher than 0.5:100, the adsorption performance of the composite material decreases. When the activation temperature is low, it is difficult to activate effectively, resulting in a decrease in the adsorption performance of the composite material. When the activation temperature is too high, the attapulgite rod structure collapses, resulting in a sharp decrease in the specific surface area and pore size, which leads to a decrease in the adsorption performance of the composite material.

[0043] (4) In the calcination and carbonization step of the preparation method of the Qinglongyi-attapulgite composite material of the present invention, the calcination and carbonization temperature is not higher than 500°C, so that the Qinglongyi biochar is well preserved and not completely carbonized, thereby improving the adsorption performance of the composite material.

[0044] (5) In the application of antibiotic adsorption, the Qinglongyi-attapulgite composite material prepared in the embodiments of the present invention has good adsorption effect due to its large specific surface area and rich pore size distribution. For example, in Example 2, the Qinglongyi-attapulgite composite material has good adsorption performance for tetracycline (TC) and oxytetracycline hydrochloride (OTC) in tetracycline antibiotics; 0.1 g / L Qinglongyi-attapulgite composite material reached adsorption equilibrium for TC in 60 min, with an equilibrium adsorption capacity of 622.6 mg / g, and reached adsorption equilibrium for OTC in 120 min, with an equilibrium adsorption capacity of 470.4 mg / g.

[0045] (6) The *Gynostemma pentaphyllum*-attapulgite composite material of the present invention is practically feasible for adsorbing and removing tetracycline and oxytetracycline hydrochloride in livestock and aquaculture. In Example 4, the *Gynostemma pentaphyllum*-attapulgite composite material removed TC in tap water and Yellow River water commonly used in livestock and aquaculture, with adsorption capacities of 378.3 mg / g and 383.1 mg / g, respectively, which is only slightly different from the TC adsorption and removal in laboratory deionized water and ultrapure water. In the example, the *Gynostemma pentaphyllum*-attapulgite composite material removed OTC in tap water and Yellow River water commonly used in livestock and aquaculture, with adsorption capacities of 350.7 mg / g and 368.1 mg / g, respectively, which is not much different from the OTC removal in laboratory-scale deionized water and ultrapure water. The cations and anions commonly found in livestock and poultry wastewater have little effect on the adsorption and removal of TC and OTC, indicating that the application of *Gynostemma pentaphyllum*-attapulgite composite material for adsorbing and removing tetracycline and oxytetracycline hydrochloride in livestock and aquaculture is stable and feasible.

[0046] (7) The dinosaur coat-attapulgite composite material of the present invention has good recyclability in application; in Example 5, after the dinosaur coat-attapulgite composite material adsorbs and removes TC and regenerates adsorbent 4 times, the adsorption amount is still around 441.7 mg / g, and the removal rate is maintained at about 84%; after adsorbing and removing OTC and regenerating adsorbent 3 times, the adsorption amount is kept constant at around 421.7 mg / g, and the removal rate is maintained at about 80%. This shows that the material of the present invention has good recyclability and good application potential.

[0047] (8) The raw materials used in the preparation of the Qinglongyi-attapulgite composite material of the present invention are widely available, inexpensive and easy to obtain; attapulgite is taken from soil and used in water, which is ecologically friendly; Qinglongyi is taken from agricultural waste in nature, turning waste into treasure and realizing the effective use of natural resources. The preparation method of Qinglongyi-attapulgite composite material is simple to operate and can adsorb and remove tetracycline antibiotics (tetracycline, oxytetracycline hydrochloride) in livestock and aquaculture wastewater. After adsorption, no secondary pollution is generated, which is ecologically friendly to water bodies. Attached Figure Description

[0048] Figure 1 The image shown is a SEM image of the dinosaur coat-attapulgite composite material from Example 1.

[0049] Figure 2 The image shows the adsorption effect of different concentrations of the dinosaur coat-attapulgite composite material on the removal of TC in Example 2.

[0050] Figure 3 The image shows the adsorption effect of different concentrations of *Cotyledon tomentosa*-attapulgite composite material in Example 2 on the removal of OTC.

[0051] Figure 4 The graph shows the adsorption effects of TC and OTC on different cations in the Qinglongyi-attapulgite composite material in Example 3.

[0052] Figure 5 The graph shows the adsorption effects of TC and OTC on the Qinglongyi-attapulgite composite material in different water bodies in Example 4.

[0053] Figure 6 The graph shows the recycling performance of the Qinglongyi-attapulgite composite material in Example 5, which adsorbs TC and OTC.

[0054] Figure 7XRD patterns of the *Gynostemma pentaphyllum*-attapulgite composite material before and after TC adsorption (ATP: purified attapulgite in Example 1; GWC: *Gynostemma pentaphyllum* powder obtained in Example 1; H-ATP-GWC-1: *Gynostemma pentaphyllum*-attapulgite composite material obtained in Example 1; TC: tetracycline (TC); H-ATP-GWC-1-TC: material of *Gynostemma pentaphyllum*-attapulgite composite material (0.1 g / L) after TC adsorption in Example 2).

[0055] Figure 8 XRD patterns of the *Tetracentron sinense*-attapulgite composite material before and after adsorption of OTC (ATP: purified attapulgite in Example 1; GWC: *Tetracentron sinense* powder obtained in Example 1; H-ATP-GWC-1: *Tetracentron sinense*-attapulgite composite material obtained in Example 1; OTC: oxytetracycline hydrochloride; H-ATP-GWC-1-OTC: material of *Tetracentron sinense*-attapulgite composite material (0.1 g / L) after adsorption of OTC in Example 2). Detailed Implementation

[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the term “and / or” as used herein includes any and all combinations of one or more of the associated listed items.

[0057] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0058] As used herein, the term “about” is used to provide for the flexibility and imprecision associated with a given term, measure, or value. Those skilled in the art can readily determine the degree of flexibility for a particular variable.

[0059] Concentration, amount, and other numerical data may be presented in range format herein. It should be understood that such range format is used solely for convenience and brevity and should be flexibly interpreted to include not only the values ​​explicitly stated as the limits of the range, but also all individual values ​​or subranges encompassed within the range, as if each value and subrange were explicitly stated. For example, a range of values ​​from about 1 to about 4.5 should be interpreted to include not only the explicitly stated limits of 1 to 4.5, but also individual numbers (such as 2, 3, 4) and subranges (such as 1 to 3, 2 to 4, etc.). The same principle applies to ranges that describe only a single value, such as “less than about 4.5,” which should be interpreted to include all the aforementioned values ​​and ranges. Furthermore, this interpretation should apply regardless of the breadth of the range or characteristic described.

[0060] The present invention will be further described below with reference to specific embodiments.

[0061] Example 1

[0062] Example of preparation of Qinglongyi-attapulgite composite material

[0063] (1) Raw material preparation:

[0064] Take 100g of crude attapulgite ore of about 60 mesh and purify it. Add 0.3g of sodium hexametaphosphate and deionized water at a mass ratio of attapulgite to water of 1:8. The purification and dispersion temperature is 65℃, the purification and dispersion stirring rate is 300r / min, and the stirring time is 3h. Centrifuge the slurry at a speed of 3000r / min for 10min. Freeze-dry the supernatant slurry for 24h to obtain attapulgite, and grind it to 100 mesh.

[0065] Take 50g of green walnut skin obtained from the fruit and vegetable market in Lanzhou, Gansu. Wash it to remove impurities until there is no liquid or turbidity, and obtain the green walnut skin. Freeze-dry it and grind it to 100 mesh to make green walnut skin powder.

[0066] (2) Activation step: Mix attapulgite and corydalis powder in a 1:1 mass ratio (1.0g each of attapulgite and corydalis powder), and add 10ml of Zn at a concentration of 0.1mg / mL. 2+ The (zinc nitrate hexahydrate) activation solution was stirred at 200 r / min until the color was uniform, transferred to the PTFE reactor liner, the reactor was installed, and the reactor was placed in a 120℃ oven for activation reaction for 24 h.

[0067] (3) Preparation of the precursor of the Qinglongyi-attapulgite composite material: Take out the activated reaction liquid, centrifuge to obtain solid, wash until neutral, freeze dry for 12h to obtain the Qinglongyi-attapulgite composite material precursor, grind to 100 mesh for later use.

[0068] (4) Calcination and carbonization: The precursor of the Qinglongyi-attapulgite composite material was placed in a 5ml corundum crucible and calcined and carbonized in a tube furnace. The calcination conditions were: N2 atmosphere, heating rate of 5℃ / min, calcination temperature of 450℃, and holding temperature for 3h to obtain the Qinglongyi-attapulgite composite material. The Qinglongyi-attapulgite composite material was dried in a desiccator to constant weight (about 2.0g) for later use.

[0069] In this embodiment, the attapulgite-coated corydalis composite material contains approximately 49.98% attapulgite by mass (based on the amount of attapulgite added); the zinc ion content, determined and calculated by ICP, is approximately 0.033% of the attapulgite-coated corydalis composite material; and the specific surface area of ​​the attapulgite-coated corydalis composite material is 89.72 m². 2 / g, its SEM image is as follows Figure 1As shown.

[0070] Example 2

[0071] Adsorption performance of dinoflagellate-attapulgite composite material for tetracycline (TC) and oxytetracycline hydrochloride (OTC)

[0072] (1) The solid dinoflagellate-attapulgite composite material obtained in Example 1 was added to 10 mL of antibiotic solutions of different specific concentrations to prepare dinoflagellate-attapulgite composite material solutions with final concentrations of 0.1 g / L and 0.15 g / L, respectively. The final concentration of the antibiotic was: C TC 100 mg / L, C OTC 100 mg / L (V TC V OTC (10 ml); the pH was adjusted to 7 and 6 respectively using 0.01 M HCl and 0.01 M NaOH solutions, and the temperature was set at 288 K for static adsorption.

[0073] (2) Samples were taken at adsorption time intervals of 10, 20, 30, 40, 50, 60, 120, 180, 240 and 300 min respectively, and the filtrate was obtained by filtering with a 0.45 μm filter. The absorbance of the filtrate after adsorption was measured by a UV-2700 ultraviolet spectrophotometer at OTC around 268 nm and 353 nm, and TC around 283 nm and 362 nm, so as to obtain the equilibrium adsorption concentration and adsorption amount.

[0074] like Figure 2 (TC) and Figure 3 As shown in (OTC), the results indicate that the 0.1 g / L dinosauroides-attapulgite composite material reached adsorption equilibrium for TC in 60 min, with an equilibrium adsorption capacity of 622.6 mg / g; the 0.1 g / L dinosauroides-attapulgite composite material reached adsorption equilibrium for OTC in 120 min, with an equilibrium adsorption capacity of 470.4 mg / g.

[0075] Example 3

[0076] Adsorption performance of *Cynanchum paniculatum*-attapulgite composite material for tetracycline (TC) and oxytetracycline hydrochloride (OTC) under ion interference conditions

[0077] (1) Prepare 10 mL of TC solutions containing KH2PO4, (NH4)2HPO4, ZnCl2, Cu(NO3)2, and Al2(SO4)3 respectively, wherein C TCThe concentration of the metal salt or ammonium salt was 100 mg / L, and the mass concentration of the metal salt or ammonium salt was 0.05 mg / mL. The pH was adjusted to 7 using 0.01 M HCl and 0.01 M NaOH solutions. Then, the dinoflagellate-attapulgite composite material prepared in Example 1 was added to make the final mass concentration of the dinoflagellate-attapulgite composite material 0.1 g / L. The mixture was then allowed to stand at 288 K for adsorption.

[0078] (2) Prepare 10 mL of OTC solutions containing KH₂PO₄, (NH₄)₂HPO₄, ZnCl₂, Cu(NO₃)₂, and Al₂(SO₄)₃ respectively, wherein C OTC The concentration of the metal salt or ammonium salt was 100 mg / L, and the pH was adjusted to 6 using 0.01 M HCl and 0.01 M NaOH solutions. Then, the dinoflagellate-attapulgite composite material prepared in Example 1 was added to make the final mass concentration of the dinoflagellate-attapulgite composite material 0.1 g / L, and it was allowed to stand for adsorption at a temperature of 288 K.

[0079] (3) After adsorption for 180 min, samples were taken and filtered with a 0.45 μm filter to obtain the filtrate. The absorbance of the filtrate after adsorption was measured by a UV-2700 ultraviolet spectrophotometer at wavelengths around 353 nm (OTC) and 362 nm (TC) to obtain the equilibrium adsorption concentration and adsorption amount.

[0080] like Figure 4 As shown, the results indicate that the Qinglongyi-attapulgite composite material can withstand large amounts of cations such as Al in actual agricultural wastewater. 3+ Cu 2+ Zn 2+ K + NH4 + Even under the presence of these conditions, the composite material still exhibits excellent adsorption and removal effects on tetracycline and oxytetracycline hydrochloride, indicating that the Qinglongyi-attapulgite composite material has practical application potential in the removal of tetracycline antibiotics from actual agricultural wastewater.

[0081] Example 4

[0082] Adsorption performance of *Cyperus diffusa*-attapulgite composite material for tetracycline (TC) and oxytetracycline hydrochloride (OTC) under real water sample conditions

[0083] (1) The filtrate was obtained by filtering the Yellow River water and tap water in Lanzhou with filter paper. 100 mg / L TC solution and OTC solution were prepared by using ultrapure water, deionized water, tap water and Yellow River water as the solution.

[0084] (2) Take 10 mL of 100 mg / L TC solution and OTC solution, and adjust the pH to 7 (TC) and 6 (OTC) respectively with 0.01 M HCl and 0.01 M NaOH solution. Then add the dinosaur-attapulgite composite material prepared in Example 1 to make the final concentration of dinosaur-attapulgite composite material 0.1 g / L, and let it stand at 288 K for adsorption.

[0085] (3) After adsorption for 180 min, samples were taken and filtered with a 0.45 μm filter to obtain filtrate. The absorbance of OTC at wavelengths of 268 nm and 353 nm and TC at wavelengths of 283 nm and 362 nm was measured by a UV-2700 ultraviolet spectrophotometer to obtain the equilibrium adsorption concentration and adsorption amount.

[0086] like Figure 5 As shown, the results indicate that the 0.1 g / L *Coprinus comatus*-attapulgite composite material removed TC (378.3 mg / g) and OTC (350.7 mg / g) from tap water and Yellow River water, respectively. The *Coprinus comatus*-attapulgite composite material of this invention can not only be applied to the adsorption of tetracycline antibiotics in ultrapure water at the laboratory scale, but also has wide applicability in actual aquaculture water bodies, such as tap water and Yellow River water, demonstrating excellent adsorption and removal of tetracycline antibiotics from aquaculture wastewater. This indicates that the *Coprinus comatus*-attapulgite adsorption material of this invention has broad practical application potential.

[0087] Example 5

[0088] Cyclic adsorption performance of dinoflagellate-attapulgite composite material for tetracycline (TC) and oxytetracycline hydrochloride (OTC)

[0089] (1) The Qinglongyi-attapulgite composite material after adsorbing TC and OTC in Example 2 (0.1 g / L Qinglongyi-attapulgite composite material group) was centrifuged and washed until the solution was neutral, and then vacuum dried at 80°C for 12 h.

[0090] (2) Place the dried material from (1) into a 5ml corundum crucible and regenerate the material at 400℃ under N2 atmosphere, repeating the regeneration 1 to 7 times;

[0091] (3) After each regeneration, prepare the regenerated *Cyclocarya paliurus*-attapulgite composite material in (2) with a final concentration of 0.1 g / L for adsorption. TC 100 mg / L, C OTC 100 mg / L (V TC V OTCThe solution was prepared in 10 ml, and the pH was adjusted to 7 (TC) and 6 (OTC) with 0.01 M HCl and 0.01 M NaOH solutions, respectively. The temperature was 288 K, and the solution was allowed to stand for adsorption.

[0092] (4) After adsorption for 180 min, samples were taken and filtered with a 0.45 μm filter to obtain filtrate. The absorbance of the filtrate after adsorption was measured by a UV-2700 ultraviolet spectrophotometer at wavelengths near 268 nm and 353 nm for OTC and 283 nm and 362 nm for TC, so as to obtain the equilibrium adsorption concentration and adsorption amount.

[0093] like Figure 6 As shown, after the *Coprinus urinaria*-attapulgite composite material adsorbed and removed TC and was regenerated four times, the adsorption capacity remained around 441.7 mg / g; after adsorbing and removing OTC and being regenerated three times, the adsorption capacity remained constant around 421.7 mg / g. These results indicate that the *Coprinus urinaria*-attapulgite composite material of this invention has excellent recyclability. The *Coprinus urinaria*-attapulgite composite material can still exhibit good adsorption and removal effects on tetracycline antibiotics even after five cycles of regeneration. This demonstrates that the *Coprinus urinaria*-attapulgite composite material of this invention has the potential for energy-saving and high-efficiency applications.

[0094] like Figure 7 and Figure 8 As shown, XRD characterization was performed on the *Coprinus comatus* powder, attapulgite, *Coprinus comatus*-attapulgite composite material in Example 1, and the *Coprinus comatus*-attapulgite composite material (0.1 g / L) adsorbed with TC or OTC in Example 2. In Example 2, the XRD pattern of the *Coprinus comatus*-attapulgite composite material after adsorption showed characteristic peaks for TC and OTC, respectively. The XRD results indicate that the *Coprinus comatus*-attapulgite composite material has the ability to adsorb TC and OTC.

[0095] Example 6

[0096] Example of preparation of Qinglongyi-attapulgite composite material

[0097] All other steps are the same as those in Example 1, except that in step (2) activation step, the mass ratio of attapulgite to cyanocotyledon powder is 1:2.

[0098] The *Gynostemma pentaphyllum*-attapulgite composite material obtained in this embodiment, under the same adsorption conditions as in Example 2, showed that the equilibrium adsorption capacity of 0.1 g / L *Gynostemma pentaphyllum*-attapulgite composite material H-APT-GWC-0.5 for TC was 264.4 mg / g and the equilibrium adsorption capacity for OTC was 178.6 mg / g. The adsorption effect was slightly lower than that of the *Gynostemma pentaphyllum*-attapulgite composite material obtained in Example 1.

[0099] Example 7

[0100] Example of preparation of Qinglongyi-attapulgite composite material

[0101] All other steps are the same as those in Example 1, except that in step (2) activation step, the mass ratio of attapulgite to cyanocotyledon powder is 2:1.

[0102] The *Gynostemma pentaphyllum*-attapulgite composite material obtained in this embodiment, under the same adsorption conditions as in Example 2, showed that the equilibrium adsorption capacity of 0.1 g / L *Gynostemma pentaphyllum*-attapulgite composite material H-APT-GWC-2 for TC was 249.8 mg / g and the equilibrium adsorption capacity for OTC was 223.6 mg / g. The adsorption effect was slightly lower than that of the *Gynostemma pentaphyllum*-attapulgite composite material obtained in Example 1.

[0103] Comparative Example 1

[0104] Comparative example of Qinglongyi biochar material

[0105] Preparation: The preparation method was the same as in Example 1, and the raw material was all prepared from *Cyclocarya paliurus* (2.0g) to produce *Cyclocarya paliurus* biochar material.

[0106] In the adsorption experiment under the same conditions as in Example 2, the biochar material obtained in this comparative example showed a lower adsorption capacity for tetracycline than the composite material obtained in Example 1. Specifically, the equilibrium adsorption capacity for TC was determined to be 125.6 mg / g using the method in Example 2, which is lower than the equilibrium adsorption capacity for TC of the biochar material obtained in Example 1.

[0107] Comparative Example 2

[0108] Comparative examples of attapulgite materials

[0109] Preparation: The preparation method was the same as in Example 1, using attapulgite material prepared entirely from attapulgite (2.0 g).

[0110] In the adsorption experiment under the same conditions as in Example 2, the attapulgite material obtained in this comparative example showed a lower adsorption capacity for tetracycline than the composite material obtained in Example 1. Specifically, the equilibrium adsorption capacity for TC was determined to be 232.3 mg / g using the method in Example 2, which is lower than the equilibrium adsorption capacity for TC of the tartaric acid-attapulgite composite material obtained in Example 1.

[0111] Comparative Example 3

[0112] Comparative example of Qinglongyi-attapulgite composite material

[0113] All other steps are the same as in Example 1, except that step (2) activation step is missing. Zn is directly applied... 2+The solution is replaced with water to carry out the precursor preparation process in step (3).

[0114] In the adsorption experiment, the adsorption capacity of the *Gynostemma pentaphyllum*-attapulgite composite material obtained in this comparative example for tetracycline or oxytetracycline hydrochloride was lower than that of the composite material obtained in Example 1. Specifically, the equilibrium adsorption capacity for TC was determined to be 125.6 mg / g and the equilibrium adsorption capacity for OTC was 108.8 mg / g using the method in Example 2. This result is much lower than the equilibrium adsorption capacity of the *Gynostemma pentaphyllum*-attapulgite composite material for TC or OTC obtained in Example 1.

[0115] Comparative Example 4

[0116] Comparative example of Qinglongyi-attapulgite composite material

[0117] All other steps are the same as those in Example 1, except that in step (2) activation step: take attapulgite and corydalis powder in a mass ratio of 1:1 and mix them (1.0g each of attapulgite and corydalis powder), and add 10ml of Zn at a concentration of 0.1mg / mL. 2+ The (zinc nitrate hexahydrate) activation solution is stirred at 200 rpm until the color is uniform. No further hydrothermal activation is required before proceeding to the next step.

[0118] In the adsorption experiment, the adsorption capacity of the *Cotyledonium styracifolium*-attapulgite composite material obtained in this comparative example for tetracycline or oxytetracycline hydrochloride was lower than that of the composite material obtained in Example 1. Specifically, the equilibrium adsorption capacity for TC was determined to be 212.5 mg / g and the equilibrium adsorption capacity for OTC was 143.4 mg / g using the method in Example 2. This result is much lower than the equilibrium adsorption capacity of the *Cotyledonium styracifolium*-attapulgite composite material for TC or OTC obtained in Example 1.

[0119] Comparative Example 5

[0120] Comparative example of glucose-attapulgite composite materials

[0121] All other steps are the same as those in Example 1, except that glucose is used instead of cyanine leaves.

[0122] In the adsorption experiment, the glucose-attapulgite composite material obtained in this comparative example showed lower adsorption capacity for tetracycline or oxytetracycline hydrochloride than the composite material obtained in Example 1. Specifically, the equilibrium adsorption capacity for TC was determined to be 309.5 mg / g and the equilibrium adsorption capacity for OTC was 243.5 mg / g using the method in Example 2. This result is lower than the equilibrium adsorption capacity for TC or OTC of the gentian-attapulgite composite material obtained in Example 1.

[0123] Comparative Example 6

[0124] Comparative example of Qinglongyi-attapulgite composite material

[0125] All other steps are the same as those in Example 1, except that the carbonization temperature in step (3) is 550°C.

[0126] In the adsorption experiment, the amount of tetracycline adsorbed by the *Cyclocarya paliurus*-attapulgite composite material obtained in this comparative example was lower than that of the composite material obtained in Example 1. Specifically, the equilibrium adsorption amount of TC was determined to be 172.8 mg / g using the method in Example 2, which is lower than the equilibrium adsorption amount of TC by the *Cyclocarya paliurus*-attapulgite composite material obtained in Example 1.

[0127] Comparative Example 7

[0128] All other steps are the same as those in Example 1, except that: the Zn in step (2) is... 2+ The ion concentration was increased to 0.5 mg / ml, using the following activation steps:

[0129] (2) Activation step: Mix attapulgite and corydalis powder in a 1:1 mass ratio (1.0g each of attapulgite and corydalis powder), and add 10ml of Zn at a concentration of 0.5mg / mL. 2+ The (zinc nitrate hexahydrate) activation solution was stirred at 200 r / min until the color was uniform, then transferred to the PTFE reactor liner. The reactor was then installed and placed in a 120℃ oven for activation reaction for 24 h.

[0130] The *Gynostemma pentaphyllum*-attapulgite composite material obtained in this comparative example was tested for Zn by ICP. 2+ And the Zn content in the Qinglongyi-attapulgite composite material was calculated. 2+ The mass percentage is 0.234% of the dinosaur-attapulgite composite material.

[0131] The adsorption capacity of TC was determined to be 208.5 mg / g and the adsorption capacity of OTC was 130.5 mg / g using the method in Example 2.

[0132] The above description provides an illustrative overview of the present invention and its embodiments. This description is not restrictive, and the embodiments shown are merely one example of the invention's implementation. Actual implementations are not limited to these examples. Therefore, if those skilled in the art are inspired by this description and design similar implementations and examples without departing from the spirit of the invention, such designs should fall within the scope of protection of the present invention.

Claims

1. A Qinglongyi-attapulgite composite material, characterized in that, Based on the weight of the Qinglongyi-attapulgite composite material, the Qinglongyi-attapulgite composite material comprises: Biochar derived from the Azure Dragon Robe; Attapulgite; the mass percentage of the attapulgite accounts for 30-60% of the patina-attapulgite composite material; And zinc ions; the zinc ions account for 0.01~0.05% of the mass percentage of the diatomaceous earth-attapulgite composite material; The preparation method of the Qinglongyi-attapulgite composite material includes the following steps: The activation step involves activating the attapulgite and calcite with zinc ions under hydrothermal conditions; the activation temperature in this step is 100~150℃, and the activation time is 18~36h. The precursor preparation step involves preparing a *Gynostemma pentaphyllum*-attapulgite precursor using zinc ion-activated attapulgite and *Gynostemma pentaphyllum*; the mass ratio of zinc ions to attapulgite is 0.02~0.1:100; and... The calcination and carbonization step involves calcining and carbonizing the *Cynanchum paniculatum*-attapulgite precursor to obtain the *Cynanchum paniculatum*-attapulgite composite material.

2. The Qinglongyi-attapulgite composite material according to claim 1, characterized in that, The specific surface area of ​​the Qinglongyi-attapulgite composite material is not less than 60m². 2 / g.

3. A method for preparing a Qinglongyi-attapulgite composite material, characterized in that, Includes the following steps: The activation step involves activating the attapulgite and calcite with zinc ions under hydrothermal conditions; the activation temperature in this step is 100~150℃, and the activation time is 18~36h. The precursor preparation step involves preparing a patina-attapulgite precursor using zinc ion-activated attapulgite and patina; the mass ratio of zinc ions to attapulgite is 0.02~0.1:

100. as well as, The calcination and carbonization step involves calcining and carbonizing the *Cynanchum paniculatum*-attapulgite precursor to obtain the *Cynanchum paniculatum*-attapulgite composite material.

4. The preparation method according to claim 3, characterized in that, In the activation step, the mass ratio of the attapulgite to the azurite is 0.5~2:

1.

5. The preparation method according to claim 3, characterized in that, In the activation step, the concentration of zinc ions is 0.05~0.2 mg / mL.

6. The preparation method according to claim 3, characterized in that, In the calcination and carbonization step, an inert gas atmosphere is used, the heating rate is 5~10℃ / min, the calcination and carbonization temperature is 450~500℃, and the calcination and carbonization time is 3~5h.

7. The application of the *Cotyledon tomentosa*-attapulgite composite material of claim 1 or 2, or the *Cotyledon tomentosa*-attapulgite composite material obtained by any one of claims 3 to 6, in the adsorption of antibiotics in wastewater.

8. The application according to claim 7, characterized in that, The wastewater is livestock and aquaculture wastewater; the antibiotic is a tetracycline antibiotic.

9. The application according to claim 8, characterized in that, The dinosaur coat-attapulgite composite material is regenerated by calcination at 400~420℃ in an inert gas atmosphere.

Citation Information

Patent Citations

  • Nitrogen and phosphorus co-doped peanut shell charcoal and preparation method and application thereof

    CN111821949A

  • Preparation method of calcium modified straw biochar and method for synchronously adsorbing phosphate and tetracycline by using calcium modified straw biochar

    CN115055159A

  • Modified biochar, preparation method thereof and application of modified biochar in preparation of tetracycline adsorption material

    CN115920842A

  • Method for preparing attapulgite / carbon adsorbent based on hydrothermal-activation coupling technology

    CN104289178A

  • Modified charcoal / attapulgite composite material as well as preparation method and application thereof

    CN114870800A